Three roads to development: Need for grounded praxis approach to strategic management and policy making - Sharma, Subhash (2007)
The approach to strategic management in case of development organisations essentially involves honing of core competencies. The focus of this approach should be on establishing close linkages on developing the organisation through institution building approach; preparing short and long term policies through forward engineering; and periodical measuring of performance improvement. This article discusses how these approaches can be effectively interlinked and suggests a general framework of strategic management for developmental context and development organisations. - Reproduced.
Keywords: Management